Risk factors for conversion in laparoscopic and robotic rectal cancer surgery. Issue 5 (24th January 2020) - Crippa, J.; Grass, F.; Achilli, P.; Mathis, K. L.; Kelley, S. R.; Merchea, A.; Colibaseanu, D. T.; Larson, D. W.
Abstract : Background: The aim of this study was to review risk factors for conversion in a cohort of patients with rectal cancer undergoing minimally invasive abdominal surgery. Methods: A retrospective analysis was performed of consecutive patients operated on from February 2005 to April 2018. Adult patients undergoing low anterior resection or abdominoperineal resection for primary rectal adenocarcinoma by a minimally invasive approach were included. Exclusion criteria were lack of research authorization, stage IV or recurrent rectal cancer, and emergency surgery. Risk factors for conversion were investigated using logistic regression. A subgroup analysis of obese patients (BMI 30 kg/m 2 or more) was performed. Results: A total of 600 patients were included in the analysis. The overall conversion rate was 9·2 per cent. Multivariable analysis showed a 72 per cent lower risk of conversion when patients had robotic surgery (odds ratio (OR) 0·28, 95 per cent c.i. 0·15 to 0·52). Obese patients experienced a threefold higher risk of conversion compared with non‐obese patients (47 versus 24·4 per cent respectively; P  < 0·001). Robotic surgery was associated with a reduced risk of conversion in obese patients (OR 0·22, 0·07 to 0·71). Conclusion: Robotic surgery was associated with a lower risk of conversion in patients undergoing minimally invasive rectal cancer surgery, in both obese and non‐obese patients. Abstract : The aim of this study was to investigate the risk factors for conversion in patients having minimally invasive surgery for rectal cancer. Robotic surgery was associated with a decreased risk of conversion compared with a laparoscopic approach in a high‐volume centre with long‐standing experience. Robt reduces conversion Abstract : Antecedentes: El objetivo del estudio era revisar los factores de riesgo para la conversión en una cohorte de pacientes con cáncer de recto sometidos a cirugía abdominal mínimamente invasiva. Métodos: Se realizó un análisis retrospectivo de pacientes consecutivos operados desde febrero de 2005 hasta abril de 2018. Se incluyeron pacientes adultos sometidos a resección anterior baja o resección abdominoperineal por adenocarcinoma primario de recto mediante abordaje mínimamente invasivo. Los criterios de exclusión fueron falta del consentimiento informado, cáncer de recto en estadio IV o recidivado y cirugía urgente. Los factores de riesgo para la conversión se determinaron mediante regresión logística. Se realizó un análisis de subgrupo en pacientes obesos (índice de masa corporal, IMC ≥ 30 kg/m 2 ). Resultados: Se incluyeron en el análisis un total de 600 pacientes. La tasa global de conversión fue del 9, 2%. El modelo multivariado mostró un riesgo 72% menor de conversión cuando los pacientes fueron tratados mediante cirugía robótica (razón de oportunidades, odds ratio, OR 0, 28, i.c. del 95% 0, 15‐0, 52). Los pacientes obesos presentaron un riesgo de conversión tres veces mayor en comparación con los pacientes no obesos (47, 3% versus 24, 5%, P < 0, 001). La cirugía robótica se asoció con una menor probabilidad de conversión en los pacientes obesos (OR 0, 22; i.c. del 95% 0, 07‐0, 71). Conclusión: La cirugía robótica se asoció con un menor riesgo de conversión en pacientes sometidos a cirugía mínimamente invasiva de cáncer de recto, tanto en pacientes obesos como no obesos.